Roadmap for the Implementation of Energy Efficiency in Public Buildings of the Kyrgyz Republic - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2019)
The objective of this document is to provide guidance for the development and implementation of a national energy efficiency (EE) investment program for public buildings in the Kyrgyz Republic. It begins by assessing the country’s EE potential; analyzing its institutional, legislative and financial frameworks; reviewing the market for EE supply and services; and summarizing current barriers to EE implementation in the public sector. It then provides two forward-looking chapters: a vision 2040 list of medium- and long-term targets for a sustainable, climate-resilient, safe, and low-carbon stock of public buildings in the Kyrgyz Republic by 2040, with reference to the United Nation (UN) sustainable development goals and the draft concept for the development of the fuel and energy sector of the Kyrgyz Republic until 2040; and a roadmap and accompanying catalogue of recommended measures that sets out the steps and timeframe necessary to: improve the political and regulatory framework for EE; strengthen the delivery capacities of relevant institutions and sectoral stakeholders; and scale up the nation’s EE investments in the country.